Pelatihan Membuat Sabun Transparan Bunga Telang Anggota PKK Desa PAL IX Sungai Kakap Kubu Raya - Athiah Masykuroh; Husnani; Ihsanul Arief (Empowerment: Jurnal Pengabdian Masyarakat, 2023)
The workshop on making butterfly pea transparent soap (Clitoria ternatea) was carried out with the aim of increasing the insight of PKK members of Pal IX Village, Sungai Kakap District, Kubu Raya Regency on how to use butterfly pea flowers. As we know the urban society’s interest in the butterfly pea flower was increasing nowadays. It can be seen from the increasing public interest in buying butterfly pea plants in commercial nurseries. Interesting flowers and it’s benefits for traditional medicine causes this plant in demand by the public. Transparent soap has a finer foam compared to opaque soap which is not transparent. The methods  used in this workshop were lectures and surveys by distributing questionnaires  to find out how far the level of knowledge of respondents  had changed after attending  the workshop in the form of pre-test and post-test questionnaires which were distributed before and after the training was carried out. After the workshop of making transparent butterfly pea soap, the knowledge of members of PKK Desa pal IX Sungai Kakap Kubu Raya about butterfly pea flowers and the possibility of making transparent soap preparations has been increased.